An analysis of the quality of life at work of employees of a credit cooperative (Research, Society and Development, 2020)
The Quality of Life at Work (QWL) has become essential with the evolution of organizations, as it provides a better work environment and employee performance. This study aimed to analyze the quality of life at work from the perspective of the employees of a credit union located in the north of the state of Rio Grande do Sul. For this, a descriptive research was carried out, with a quantitative approach, with data collected through the scale of Walton (1973). Thus, the dimensions analyzed were: fair and adequate compensation, use and development of skills, opportunity for growth and development, social integration at work and total work space in personal life. The investigated agency has 7 employees, who were part of the sample. The results obtained contribute strongly to the cooperative, as it was possible to understand the perception of the collaborators about the studied theme, favoring decision making.